Are All State-Owned Enterprises Equal? A Taxonomy of Economic Activities to Assess SOE Presence in the Economy - Dall-Olio, Andrea (The World Bank, 2022)
This paper proposes a sector taxonomy of the rationale for the presence of state-owned enterprises in specific industries. The taxonomy is conceptualized only on an efficiency-based rationale for state participation in different economic activities, abstracting it from social or political justification of state-owned enterprises, which can be subjective or conditioned to the country context. The taxonomy is leveraged on a standard industry classification, the Nomenclature of Economic Activities Revision 2 four-digit level sector classification, which is sufficiently disaggregated to resemble specific markets, and thus more appropriate for analyzing the presence of state-owned enterprises through the lens of industrial organization. The proposed taxonomy deploys a decision tree, based on efficiency-based criteria, to classify 563 disaggregated sectors into one of three groups: a "competitive" category, for which the presence of state-owned enterprises does not appear to be justified on grounds of economic efficiency/market failure; a "natural monopoly" category, which includes economic sectors whose market structure is characterized by economies of scale and subadditivity costs that could be corrected via the participation of state-owned enterprises; and a "partially contestable" category, which includes economic sectors characterized by some form of market power, externalities, or other market failures that could be addressed through state ownership. The application of the decision tree classifies 11 disaggregated sectors as natural monopolies, 45 as partially contestable, and the remaining 505 as competitive